2016
DOI: 10.1002/ajmg.b.32494
|View full text |Cite
|
Sign up to set email alerts
|

Highly polygenic architecture of antidepressant treatment response: Comparative analysis of SSRI and NRI treatment in an animal model of depression

Abstract: Response to antidepressant (AD) treatment may be a more polygenic trait than previously hypothesized, with many genetic variants interacting in yet unclear ways. In this study we used methods that can automatically learn to detect patterns of statistical regularity from a sparsely distributed signal across hippocampal transcriptome measurements in a large‐scale animal pharmacogenomic study to uncover genomic variations associated with AD. The study used four inbred mouse strains of both sexes, two drug treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Genotyping for rs2032583 and rs2235015 (TT/GG) may be used for clinical application to optimize antidepressant treatment [19]. Antidepressant treatment outcome was significantly associated with rs203258, rs2235015 [17], rs2032588 [13], and C3435T [83] Encodes a glutamate-gated ionic channel family protein that collectively functions as excitatory neurotransmitters in the CNS [121] The GRIK4 SNPs rs12800734 [72] and rs1954787 showed a strong association with antidepressant treatment outcome (remission and/or response) [85] GNB3 G protein subunit beta 3…”
Section: Ssris Treatment For Major Depressive Disordermentioning
confidence: 99%
See 2 more Smart Citations
“…Genotyping for rs2032583 and rs2235015 (TT/GG) may be used for clinical application to optimize antidepressant treatment [19]. Antidepressant treatment outcome was significantly associated with rs203258, rs2235015 [17], rs2032588 [13], and C3435T [83] Encodes a glutamate-gated ionic channel family protein that collectively functions as excitatory neurotransmitters in the CNS [121] The GRIK4 SNPs rs12800734 [72] and rs1954787 showed a strong association with antidepressant treatment outcome (remission and/or response) [85] GNB3 G protein subunit beta 3…”
Section: Ssris Treatment For Major Depressive Disordermentioning
confidence: 99%
“…Encodes one of the receptors for serotonin Polymorphisms in 5HT-2A receptor rs17288723 [72], rs7997012 [102,103], rs9534505 [93], rs6311, rs6313, rs7997012, and rs1928040 [91,102] were significantly associated with therapeutic response or remission to antidepressants [102] SLC6A4 Solute carrier family 6 member 4…”
Section: -Hydroxytryptamine Receptor 2amentioning
confidence: 99%
See 1 more Smart Citation
“…Sex: Strikingly, most of the studies were conducted on male animals since out of 107 cohorts only 8 involved females [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], and, in fact, RNA profiling on males and females subjected to the same paradigm was performed only four times [ 32 , 33 , 34 , 36 , 37 , 38 ]. In contrast, the proportions are much more balanced between studies in mice and rats or between studies conducted in naïve or stressed animals ( Figure 2 A–C).…”
Section: Resultsmentioning
confidence: 99%
“…[23] Other inflammatory candidate genes such as IL2 , IL10 , IL18 , tumor necrosis factor alpha ( TNF-α ) and interferon-gamma ( IFN-γ ) have received less attention, although having been previously related with major depressive disorder. [24, 25] Taking into account that response to medication may be a polygenic and complex trait than previously hypothesized and distinct molecular mechanisms seem to modulate inflammatory pathways as stated above [26], studies should address the role of different cytokine genetic variants, as response to medication may be as complex as the pathology. Besides, recent studies have also shown that alterations in the methylation status that regulate gene expression of these polymorphisms may contribute to disease risk and prognosis [27, 28], but few studies have examined whether inflammatory genes are differentially methylated in depression (Ryan’s study in late life depression [29]), or the association of methylation status of such polymorphisms with treatment outcomes.…”
Section: Introductionmentioning
confidence: 99%